UPAYA PEMERINTAH DAERAH DALAM PEMBERDAYAAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) SENTRA INDUSTRI KONVEKSI DAN BORDIR DI DESA PADURENAN, KECAMATAN GEBOG, KABUPATEN KUDUS - Definta Aliffiana; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Efforts to accelerate economic development is one of the government's strategy in empowering the community to reduce unemployment rate, one of them is Micro, Small and Medium Enterprises (UMKM), because UMKM is one of the booster for growth and economic development that has contribution in creating manpower and a source of income for the community. The existence of UMKMs not only increase income, but also in the framework of equitable income for the community. This is because of the UMKM sector can involve many people with various businesses. The role of government is needed in the effort of empowerment. The purpose of this research is to know and analyze the condition of empowerment of UMKM Convection and Embroidery Center in Padurenan Village, Gebog Sub-district, Kudus Regency. The research method used in this research is descriptive qualitative. The results showed that the efforts of local government represented by the Office of Industry, Cooperatives and UKM Kudus District in empowerment has been successful, but not maximal, because of some indicators of success of empowerment can not be given by the government, that is about providing aid funds as capital business for conventional and basket UMKM business actors. Recommendation based on this research is Local Government help to find fund aid to other private parties that exist in Kudus Regency or outside Kudus District.